EXPLORING REMOTE WORK ADOPTION AMONG FINANCE PROFESSIONALS IN A SMALL ISLAND DEVELOPING STATE: A CONCEPTUAL STUDY FOR THE POST-COVID-19 ERA - Gunnoo , Leenshya (PEOPLE: International Journal of Social Sciences, 2024)
The COVID-19 pandemic has significantly altered traditional work environments, compelling many organizations to adopt remote working models. This conceptual study explores the impact of remote work on the productivity of finance professionals in the post-COVID-19 era, particularly in Mauritius. Drawing on the Theory of Work Adjustment (TWA), the research investigates the influence of personal well-being, environmental factors, and resource constraints on work-from-home (WFH) productivity. The study aims to fill a gap in the existing literature by providing theoretical insights into the unique challenges and opportunities associated with remote work in the finance sector. The research intends to adopt a quantitative methodology, utilizing a systematically sampled survey to collect data from finance professionals. The survey instrument will be adapted from established studies, ensuring reliability and validity through rigorous pretesting and validation using the Rasch Model. Structural Equation Modelling (SEM) will be employed to analyze the relationships between the constructs, providing a comprehensive understanding of the factors influencing WFH productivity.The findings are expected to offer valuable insights for senior management and policymakers in optimizing remote work strategies, particularly in maintaining productivity and well-being among finance professionals. The study acknowledges its limitations, including the lack of empirical data and the focus on a specific sector and geographic region. Future research should address these limitations by incorporating real-world data and expanding the scope to other industries and regions, thereby enhancing the generalizability and applicability of the findings.